التباين المكاني للخضروات الورقية في شواطئ نهر دجلة في محافظة واسط لسنة 2016 ( الإستعمالات الزراعية لشواطئ نهر دجلة في محافظة واسط ) - لفته الزاملي شاكر مسير; كريم الشمري هدى عبد الحسين (Journal of College of Education, 2018)
Agriculture is considered one of the important economic activities for its big role in saving basic nutritional materials for residents because they are the source of living to the workers in this field, and according to that significance, it is often devoted the best agricultural lands in the rural and urban areas as well. In the banks areas, the competition is clearly found between the agricultural and nonagricultural uses, and even between the agricultural uses themselves, although planting leaves vegetables occupies the best lands for ages in the urban centres for each administrative unit whether it is district or not because of the need for these vegetables to be close to the markets because they are quick to decay and they are daily consumed, in addition they are low priced in accordance to the rest of vegetables, therefore they do not bear the additive costs of transportation that resulted from far away distance. This research aims at showing the portrait of agricultural distribution for planting leaves vegetables in study field, and to achieve this purpose, it was adopted corpse structure to explain that, and it depended located study (Questionnaire form and personal meetings) because of the lack of formal information that cover the subject of study, the matter which helped in identifying the planted area and the amount products for each corpse according to the real location. The planted area with leaves vegetables corpse is (174 donam), and it covers (1,29 percent) from the total planted area in the study field which contains (13453 donams). There are a variety of corpses to cover (9 corpses), with big products and good quality, and most of these vegetables planted on the whole year except some of them which planted in certain seasons such as Spanish, dill, and cress which can be planted in protected areas.